TANGGUNG JAWAB SHOPEE TERHADAP TRANSAKSI ILEGAL JUAL-BELI HEWAN DILINDUNGI DI E-COMMERCE - Tegar Hartantha Pratama, (2024)
Electronic Commerce activities are growing rapidly along with the development of technology.One of the online buying and selling transaction platforms ("E-commerce") in Indonesia is "Shopee". In its implementation, there are Shopee users who do not meet the Guidelines imposed by Shopee, the lack of supervision of goods traded through E-Commerce transactions so that there are many circulating illegal goods traded at Shopee. This writing discusses the implementation of Shopee's responsibility and liability in E-Commerce transactions based on the provisions of the Civil Code, related to the object of the transaction of buying and selling protected animals illegally at Shopee. This research method uses Normative Juridical Research using a Statute Approach The results of the study indicate that Shopee is responsible for the legal consequences due to the existence of illegal electronic information content. So it is necessary to identify violations and validate each product sold. Shopee can be legally liable based on Article 1365 of the Civil Code. It is better if Shopee as a marketplace platform as an electronic system organizer organizes its marketplace platform responsibly, safely, reliably, and builds public trust in its operation in accordance with the provisions of the Law and Shopee is also legally liable and does not divert its responsibility. Keywords: E-Commerce, Illegal, Liability